Design of a 5 1 bandwidth stripline notch array from FDTD analysis. - Kragalott, M.
A 5:1 bandwidth stripline notch array antenna is designed from parametric investigations of flare and feed dimensions. The finite-difference time-domain (FDTD) method is employed to perform the parametric studies. Both linear and planar single-polarization arrays are considered with half-wavelength element spacing at the highest frequency. The linear array elements depend upon E-plane element mutual coupling to achieve wideband behavior. Edge elements, which cannot benefit from full E-plane coupling, are shown to maintain good transmit performance with the application of amplitude tapering. The planar array is shown to have a scanability (active VSWR <2) averaging 51° off broadside in the E-plane and exceeding 60° in the H-plane. As an infinite planar array, the antenna is predicted to have a bandwidth exceeding 7:1 on broadside. Measurements are in good agreement with the computations
Keywords: 1 to 5 GHz; 5:1 bandwidth stripline notch array; E-plane element mutual coupling; FDTD analysis; H-plane.; SHF; Active VSWR; Amplitude tapering; Broadside; Edge elements; Electronic steering applications; Feed dimensions; Finite-difference time-domain method; Flare dimensions; Half-wavelength element spacing; Infinite planar array; Linear array elements; Linear single-polarization array; Measurements; Parametric studies; Planar single-polarization array; Printed stripline notch; Transmit performance; Wideband behavior